Human capital in power generation peruvian company - Santos Jiménez, Néstor (2012)
Human capital is a valuable resource whose management involves not only an adequate compensation for their work but also make him partaker of the challenges of the company, so you feel part of it and as such adopt an attitude of commitment to all stakeholders of the organization. According to public information analyzed for the period 2007- 2010, the main electricity generating companies in Peru highlights a major effort in human capital management, with attractive and competitive benefits, contributing to efficiency and competitiveness of these companies.